The impact of leadership on socio-economic development of municipalities: a comparison of Ward 10 Villages and Seshego Township within Polokwane Local Municipality - Masemola, Namane Dickson (My University, 2021)
This study focused on service delivery in Polokwane Municipality, with a special reference to the role of political and administrative leadership in providing services to the communities of Seshego Township and Ward 10 villages. The data for this study was collected using qualitative methodology. The findings indicated that service provision and infrastructure in Seshego Township and Ward 10 villages have been inadequate over the past twenty-five years of the new democratic government. The challenges impacting negatively on the communities are services not guaranteed and poor quality of water, roads, corruption, lack of development and high rate of unemployment. The study noted the importance of the role of politicians and citizens in providing services to communities within the local sphere of governance. That is, such administrators should be given the space to execute their work with minimal interference from politicians, a process aptly dubbed "de-politicisation of the public service." There was also a discussion about the immense role citizens play in service delivery within their communities, notably the substantial knowledge they have (indigenous knowledge), which should assist and enhance the evaluation of programmes and services in the communities. It was established that there is a need to strengthen political and administrative leadership accountability to communities and individual recipients. Criteria for evaluating leadership capacity and the consequences (intended and unintended) of new frameworks on leadership must be developed. Municipal leadership is vital, and the executive mayor, council, municipal manager, and senior officials must assume ownership and accountability for achieving a clean audit and lead by example. Municipal political and administrative leadership, as well as the political structures that surround them, must be acutely aware of the disastrous implications of inappropriate behaviour and political interference on socio-economic development and municipal service delivery. The findings of the study confirmed the need for improved sustainable service delivery and socio-economic development. Rural development remains an important programme that must be pursued to successfully reduce poverty and conditions that denigrate people's well-being in rural areas. To ensure adequate and high-quality service delivery, appropriate public policies and a legislative framework must be implemented. It is evident that infrastructure development and job creation play a significant role in rural communities. Analysis of data from the survey instrument indicated that views expressed by community members differed substantively from the views sourced from interviews with municipal officials. The literature reviewed is aligned with the findings of the empirical study and the views expressed by the participants of the study were appropriate and credible. It is, therefore, evident that the municipality must improve its service delivery and socio-economic development strategies. Clientelism was thoroughly examined in the study since it has a detrimental impact on the process of municipal service delivery. The main areas investigated in this study are political leadership and socio-economic development. The study culminated with an exposition of the presentation of findings from the municipality and its members, as well as the findings from the document analysis, which confirmed the role of politicians and municipal officials within the Polokwane Local Municipal Council. Lastly, the study briefly outlined summary, conclusion, and recommendations.
Thesis (Ph.D. (Public Administration)) -- University of Limpopo, 2021
Keywords: Leadership; Clientelism; Service delivery; Municipality; Poverty; Employment opportunities; Leadership; Poverty -- South Africa.; Job vacancies; Economic development -- South Africa -- Limpopo; Municipal government -- South Africa -- Limpopo; Political leadership -- South Africa -- Limpopo